THE EFFECT OF FRAUD PENTAGON ON FINANCIAL STATEMENT FRAUD WITH COMPANY SIZE AS A MODERATING VARIABLE IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2021–2024 - Enzlika Mirandha; Erlina; Ibnu Austrindanney Sina Azhar (RADJA PUBLIKA, 2026)
This study aims to analyze the effect of the fraud pentagon, proxied by financial targets, financial stability, ineffective monitoring, auditor changes, changes in directors, and the frequency of CEO photos, on financial statement fraud, and to examine the moderating role of firm size. The population consists of manufacturing companies listed on the Indonesia Stock Exchange from 2021 to 2024. Using purposive sampling, a sample of 130 companies was obtained, totaling 520 observations. Financial statement fraud was measured using the Fraud Score Model (F-Score). Data analysis was conducted using panel data regression with the Common Effect Model (CEM) approach via EViews 12. The results show that financial targets have a positive and significant effect on financial statement fraud. Conversely, financial stability, ineffective monitoring, auditor changes, changes in directors, and the frequency of CEO photos have no significant effect. Simultaneously, all independent variables significantly influence financial statement fraud. Furthermore, firm size does not moderate any of these relationships. These findings indicate that the pressure to achieve financial targets is the main driver of financial statement fraud in manufacturing companies